UR_GERICHTE 2013_OG V 13 13. vom 30. August 2013 - UR Obergericht (2013)
IV. Art. 8, Art. 21 Abs. 2 IVG, Art. 2 HVI, Ziff. 9.02 HVI-Anhang, Rz. 2083 KHMI. Hilfsmittel. Anspruch auf ein Rollstuhlzuggerät.